Optimalisasi Penataan Access Point Menggunakan Algoritma Genetika (Studi Kasus Gedung Graha Merah Putih) - Ramadhan Imam Dzaky; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Laying out a good Wi-fi System requires optimizing the power level which is received from the transmitter to the receiver. The most influential value in determining the performance of the Wi-fi system is the value of the power level, because this value used to determine the coverage area of a transmitter (access point). Using genetic algorithms due to the existence of various references and as suitable algorithm for problems related to optimization. This algorithm can find the best solution from various possible solutions quickly and efficiently compared to other algorithms. Research conducted optimization by comparing the results of optimization with the existing conditions. The purpose of optimization is to arrange access point to produce efficient signal coverage and strength. The research location is on the 6th and 10th floor of the PT. Telkom Witel Rider Building. In the 6th floor there are 13 access points with the coverage area increasing to 59.2% with the signal strength being at -70 dBm to -75 dBm. This research is conducted to find out the ideal position and number of access points. The total access points needed are 13 pieces with a coverage area of 59.2%, and the signal strength value being -70 dBm to -75 dBm. Keyword: Genetic Algorithm, Wi-Fi, Access Point, Coverage Area, Signal Strength